USM MINDFUL OF STUDENTS’ WELFARE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 5 January 2016 - Universiti Sains Malaysia (USM) has always been mindful on issues concerning the students’ welfare.